JURNALISME ERA DIGITAL: DIGITALISASI JURNALISME DAN PROFESIONALITAS JURNALISME ONLINE - Muliawanti, Lintang (LENTERA: Jurnal Ilmu Dakwah dan Komunikasi, 2018)
Rapid technological progress, encourage journalism industry contributed penetrated on digitization, with the emergence of the phenomenon of online journalism. In the era of online journalism itself, journalists are required to follow the conditions of the readers in the virtual world, where information is required for fast-paced. But on the other hand, online journalists are also required to have more skills than conventional journalists, where the skills in providing both visual and writing content are also required to be faster and creative in innovating the appearance of news and information in writing in multiplatform. The journalistic skills required for this versatility create problems that arise, namely the professionalism of journalists themselves, in which the process of collecting news, processing, and presenting news is not in accordance with the ethics of professionalism of online journalists. This paper aims to find out how the problems and professionalism of online journalism. The positive impact of the professionalism of online journalism includes being required to be more skilled in the provision of both visual and writing content, as well as being required to be faster and creative in innovating the appearance of news and information. But in addition there are other problems, first about the collection of news that is vulnerable to plagiarism. Second, about news reporting, which shifts the practice of "pre-verification" to "post-verification", and third on the aspect of presenting the news, which gave birth to the title journalism phenomenon.Keyword: Journalistic Digitalization, Convergence, Â New media, Online Journalism, Online Professionalism Journalism, Digital Communication